Ischemic Stroke and Bleeding: Clinical Benefit of Anticoagulation in Atrial Fibrillation After Intracerebral Hemorrhage. Issue 3 (March 2020) - Stanton, Robert J.; Eckman, Mark H.; Woo, Daniel; Moomaw, Charles J.; Haverbusch, Mary; Flaherty, Matthew L.; Kleindorfer, Dawn O.
Abstract : Background and Purpose—: Patients with intracerebral hemorrhage (ICH) and atrial fibrillation (AF) are at risk for ischemic events. While risk calculators (CHA2 DS2 -VASc and HAS-BLED) have been validated to assess risk for ischemic stroke and major bleeding in AF patients, decisions about anticoagulation must consider the net clinical benefit of anticoagulation. Furthermore, stroke and bleeding risk are highly correlated, making decisions more difficult. Methods—: We examined patients in the GERFHS III study (Genetic and Environmental Risk Factors for Hemorrhagic Stroke)—a population-based retrospective study of spontaneous ICH patients without a structural or traumatic cause in the Greater Cincinnati/Northern Kentucky region between July 2008 and December 2012. CHA2 DS2 -VASc and HAS-B(L)ED (minus L because labile international normalized ratio was unavailable) scores were calculated for ICH patients with AF. Using a Markov state transition model, we estimated net clinical benefit of anticoagulation relative to no treatment in quality-adjusted life years (QALYs). We defined minimal clinically relevant benefit as 0.1 QALYs. Results—: Among 1186 cases of spontaneous ICH, 95 cases had AF and met our survival criteria. Within 1 year, 8 of 95 (8%) would be expected to have a major bleeding event on anticoagulation, and 5 of 95 (5%) of patients would be expected to have an ischemic stroke off anticoagulation. Sixty-eight of 95 (71%) patients would have higher risk for major bleeding than for ischemic stroke. Anticoagulation with directly acting anticoagulants would result in no clinically significant gain or loss in 73%. Roughly 12% would gain >0.1 QALYs, and 15% would lose >0.1 QALYs. Among patients receiving aspirin, most have no significant net clinical benefit or loss. Overall, anticoagulation of the entire cohort would result in an aggregate loss of 0.92 QALYs. Conclusions—: Our analysis suggests that universal anticoagulation after ICH would be associated with a net loss of QALY. Additional factors should be considered before anticoagulating patients with AF after ICH. Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00930280. Abstract : Supplemental Digital Content is available in the text.